Impact of Corporate Governance on Return of Equity: Insights from Muscat Securities Market: Examining the Impact of Corporate Governance Mechanisms on Return on Equity in Muscat Securities Market (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Purpose – To investigate and conclude the impact of corporate governance mechanisms namely board size, concentrated ownership, number of audit committees on the return on equity. The paper focuses on companies listed on Muscat Securities Market.Research Design – Data for forty-five companies across financial, industrial, and service sectors was collected from Capital Market Authority of Oman for a period of ten years (2010-2019). In total there were 450 observations which were then reduce to 45 observations taking average of ten years. STATA was used for data analytics.FindingsTakeaways – The research discovered that chosen independent variables had a relation with return on equity. This is consistent with much research particularly in the developing and emerging economies. Board size demonstrated a positive relation, however concentrated ownership and number of audit committees demonstrated a negative relation with return on equity. ROE showed positive correlation with board size and number of audit committee meetings and a negative correlation with concentrated ownership.ContributionValue – There have been very less studies investigating the impact and relationship of corporate governance on ROE. Further a study across sector is also not evident. This study present valuable insights from Muscat Securities Market and comparing them with other findings from various parts of the world. The intent for the contribution to filed of academics is to provide valuable findings for various stakeholders in understanding what is corporate governance and how they channelize the framework to improve the return on equity.